Step 1: Determine the conjugate of the denominator. ( to find the conjugate just change the sign of the imaginary part ).
In this example, the conjugate of $ \color{orangered}{ 3+2i }\, $ is $ \color{blue}{ 3-2i } $.
Step 2: Multiply both the numerator and denominator by the conjugate:
$$\begin{aligned} \frac{ 2+i }{ 3+2i } &= \frac{ 2+i }{ 3+2i } \cdot \frac{ \color{blue}{ 3-2i } }{ \color{blue}{ 3-2i } } = \\[1 em] &= \frac{ \left( 2+i \right) \cdot \left( 3-2i \right) }{ \left( 3+2i \right) \cdot \left( 3-2i \right) } \end{aligned} $$Step 3: Simplify numerator and denominator (use $\color{blue}{i^2 = -1}$)
$$ \begin{aligned} \left( 2+i \right) \cdot \left( 3-2i \right) &= 2 \cdot 3 + 2 \cdot \left(-2 \,i \right) + \left( 1 \,i \right) \cdot \left(3 \right) + \left( 1 \,i \right) \cdot \left(-2 \,i \right) = \\[1 em] &= 6 -4 \, i + 3 \, i -2 \color{blue}{(-1)} = \\[1 em] &= 8-i\end{aligned} $$ $$ \begin{aligned} \left( 3+2i \right) \cdot \left( 3-2i \right) &= 3 \cdot 3 + 3 \cdot \left(-2 \,i \right) + \left( 2 \,i \right) \cdot \left(3 \right) + \left( 2 \,i \right) \cdot \left(-2 \,i \right) = \\[1 em] &= 9 -6 \, i + 6 \, i -4 \color{blue}{(-1)} = \\[1 em] &= 13\end{aligned} $$Step 4: Separate real and imaginary parts:
$$ \frac{ 2+i }{ 3+2i } = \frac{ 8-i }{ 13 } = \frac{ 8 }{ 13 } + \frac{ -1 }{ 13 } i= \frac{ 8 }{ 13 }-\frac{ 1 }{ 13 }i $$